Ceremonies and Time in Shakespeare. (3rd July 2019) - Findlay, Alison
ABSTRACT: This essay considers some moments in Shakespeare's texts which exemplify the Janus-faced quality of ceremonies: their enactment in the present looking backwards to past traditions and forwards to inaugurate new social relations. The argument draws on Victor Turner's theorization of ritual as an event that gives shape to "liminality, " that which "eludes or slips through the network of classification that normally locate states and positions in cultural space, " and argues that this applies to time as well. It also considers the construction of time in terms of kairos, a moment of time infused with meaning. The essay analyses ceremony in three Shakespearean genres. First, it examines Bertram's and Helena's ring exchange in All's Well That Ends Well as a "distended" ritual that collapses time. It then turns to Richard III, unpacking its complex sequence of ceremonies of betrothal, mourning, and sovereignty that are "continuously disrupted". The final section describes the ceremonial time of romance in The Winter's Tale, unfolding the power invested in the kairotic time evoked by the oracle of Delphi, the sheep-shearing ceremony, and Paulina's "resurrection" of Hermione.